Pengukuran Kinerja Aset Ruang Terbuka Hijau di Taman Hutan Raya Gunung Kunci Sumedang - Agniawati, Alin; Suciyani, Wida Oktavia (UNISSULA Semarang, 2023)
One of the Green Open Spaces (RTH) managed by the Sumedang District Forestry and Environment Service is the Gunung Kunci Grand Forest Park. Tahura Gunung Kunci is utilized as a green open space for recreation. The physical condition of the facility assets in Tahura Gunung Kunci is currently in a sub-optimal condition. The purpose of this study was to evaluate the effectiveness of green open space assets in Tahura Gunung Kunci using criteria Urban Green Space which consists of size of area, amenities, the transportation’s park and security network, and focal point. The research method used is a descriptive method with qualitative and quantitative approaches. Research data collection was carried out through interviews, observation, and documentation studies. The results of the study show the score or performance value of green open space assets in Tahura Gunung Kunci with the interpretation of